Left-Right model with radiative double seesaw mechanism - Paulo Areyuna C.; A. E. Cárcamo Hernández; Vishnudath K. N.; Sergey Kovalenko; Roman Pasechnik; Iván Schmidt (Journal of High Energy Physics)
Abstract We propose an extended Left-Right symmetric model with an additional global U(1) X symmetry, which collapses to a residual subgroup ℤ 2 after spontaneous symmetry breaking. In this model, the light active neutrino masses are generated via a double seesaw mechanism with the Dirac submatrix arising at one loop. In addition, the masses of the charged fermions of the Standard Model (SM) that are lighter than the top quark are generated at one loop level and the residual ℤ 2 symmetry ensures the stability of the Dark Matter (DM) candidate of the model. To the best of our knowledge our model has the first implementation of the radiative double seesaw mechanism with the Dirac submatrix generated at one loop level. We show that the model can successfully account for the observed pattern of the SM fermion masses and mixing, and that it is compatible with constraints arising from the muon g-2 anomaly, neutrinoless double beta decay and DM.